GAMBARAN AKTIVITAS ENZIM Aspartat aminotransferase (AST) PADA PEROKOK AKTIF 10-15 TAHUN DI WILAYAH KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - diyan bahar diyan; Devi Cyntia Dewi; Satriani Arliza (Politeknik Kesehatan Kemenkes Bengkulu, 2023)
Problem: Smoking is one of the factors causing liver damage because there are chemicals suchastar,nicotine and carbon monoxide.Exposure to cigarette smoke that enters the body and cause lipid peroxidation which causes damage to the normal cell membrane the liver.The purpose of this study was to determine the description of the results of AST enzyme activity in active smokers 10 15 years in the Kampung Melayu District of Bengkulu City.Research Methods type of research Observational research with kineticexamination method using Ray to1904 Cphotometer.The results of research on AST enzyme activity in active smokers 10-15 years from30 samples there were 22 samples within creased AST levels (73.3%),while normal AST levels were 8 samples(26.7%).The conclusion of the study was that the activity of the enzyme aspartateaminotransferase (AST) was higher in active smokers10-15. Keywords: Cigarette, Smoker, Aspartate aminotransferase (AST)